Features of treatment of periodontal diseases in women accessing oral contraceptives - Борисенко, Анатолій Васильович; Ватанха, Тетяна Василівна (Actual Dentistry, 2019)
Summary. In the pathogenesis of periodontal diseases of women, an imbalance of sex hormones is important. It is considered as one of the provocative factors of periodontal disease. According to the literature, oral contraceptives may cause changes in periodontium similar to changes in puberty and pregnancy. It is necessary to develop appropriate therapeutic and preventive measures aimed at reducing the manifestations of inflammation in the periodontium of women who take oral contraceptives. Objective: development of methods and determine the effectiveness of drug treatment of periodontal disease in women who take hormonal contraceptives for the purpose of pregnancy planning. Material and methods. A survey was conducted on 110 women, the main group was 80 women taking oral contraceptives, control 30 women who did not take them. To quantify the state of periodontal tissues, the Schiller-Pisarev test [2], the Green-Vermillion HygieneIndex [3,4], the Gingival Index (GI) by Silness-Loe [9],the Bleeding Index by H.R. Muhlemann [7], the index PMA by S. Parma [8], the index of the dental plaque of interdental gaps (API) by Lange [6] Results. The investigation showed that inflammatory and degenerative-inflammatory diseases of the periodontal tissue were detected in 80 women in the primaryand in 30 women in the control group. They found an unsatisfactory state of oral hygiene in both groups. In 68(85,0 %) women in the primary group and 24 (80.0 %)controls, chronic catarrhal gingivitis was detected; Generalized periodontitis wasdetected in 8 (15.0 %) women in the primary group and in 6 (20.0 %) women in thecontrol group. After treatment, there was a significant improvement in oral hygiene and periodontal tissues in patients of the main group. Conclusions. Analysis of the data shows a significant level of inflammatory and dystrophic-inflammatory periodontal disease in theexamined women. Clinical andlaboratory studies have established a high efficacy of the proposed method for the treatment ofperiodontal diseases in women who take oral hormonal contraceptivesas soon as possible. Key words: periodontal disease, oral contraceptives, treatment of patients with periodontal diseases.